2021
DOI: 10.1038/s41598-021-88009-w
|View full text |Cite
|
Sign up to set email alerts
|

CAPS1 is involved in hippocampal synaptic plasticity and hippocampus-associated learning

Abstract: Calcium-dependent activator protein for secretion 1 (CAPS1) is a key molecule in vesicular exocytosis, probably in the priming step. However, CAPS1’s role in synaptic plasticity and brain function is elusive. Herein, we showed that synaptic plasticity and learning behavior were impaired in forebrain and/or hippocampus-specific Caps1 conditional knockout (cKO) mice by means of molecular, physiological, and behavioral analyses. Neonatal Caps1 cKO mice showed a decrease in the number of docked vesicles in the hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, CAPS1 can regulate the secretion and release of monoamine neurotransmitters and neuropeptides in synaptic vesicles of neuroendocrine cells. In vivo study, using CAPS1 knockout mice, it has shown that CAPS1 is an important protein in regulating the release of synaptic vesicles (Jockusch et al, 2007). Using the BDNF-GFP, study has confirmed that CAPS1 can affect BDNF secretion by regulating the secretion process of synaptic vesicles in hippocampal neurons (Eckenstaler et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, CAPS1 can regulate the secretion and release of monoamine neurotransmitters and neuropeptides in synaptic vesicles of neuroendocrine cells. In vivo study, using CAPS1 knockout mice, it has shown that CAPS1 is an important protein in regulating the release of synaptic vesicles (Jockusch et al, 2007). Using the BDNF-GFP, study has confirmed that CAPS1 can affect BDNF secretion by regulating the secretion process of synaptic vesicles in hippocampal neurons (Eckenstaler et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…However, the role of CAPS1 in brain function, especially in central nervous system‐related disease, is poorly understood. Recent study has shown that CAPS1 knockout mouse showed impairments in hippocampal long‐term potentiation (LTP), indicating the association of CAPS1 with learning ability (Ishii et al, 2021). We demonstrated for the first time that the expression of CAPS1 increased in the hippocampus after ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi staining was performed as previous study described [24].The isolated hippocampal tissue was xed with agar gel on the ice surface. Place the hippocampal tissue in a vibration section (vertical position, 380µM/piece).…”
Section: Ltp Detectionmentioning
confidence: 99%